Phonon Drag Thermopower in Quantum Wire with Parabolic Confinement Potential - Abbasov, I.I.; Hasanov, Kh.A.; Huseynov, J.I. (Металлофизика и новейшие технологии, 2017)
The quantitative theory of phonon drag thermopower for the one-dimensional electron gas in a quantum wire with a parabolic confinement potential is developed. The temperature gradient is directed along the axis of a quantum wire. As assumed, the Fermi level is located between the zero and first levels of a size quantization. Using the Boltzmann kinetic equation, the phonon and electronic parts of a thermoelectric power are calculated. For comparison, numerical calculations of the temperature and concentration dependences of the phonon and diffusion parts of a thermoelectric power are carried out. As shown, the phonon drag makes a main contribution in thermopower within the temperature interval 2–20 K.